Mathematical Curiosity, Epistemological Beliefs, and Mathematics Performance of Freshman Preservice Teachers - Belecina, Rene R; Ocampo, Jr., Jose M (MIMBAR PENDIDIKAN, 2016)
ABSTRACT: There are many factors that influence academic performance of students. Some of these are related to personological, sociological, and psychological factors. In recent years, academic achievement and performance have been linked to several psychological factors. Two of these psychological factors that may have direct impact or influence on academic performance are curiosity and epistemological beliefs. The study described the level of mathematical curiosity and epistemological beliefs of first year preservice teachers. Mathematical curiosity includes epistemic curiosity, perceptual curiosity, exploration, and absorption. Epistemological beliefs include certainty of knowledge, source of knowledge, structure of knowledge, control of knowledge acquisition (personal), control of knowledge acquisition (general), and speed of knowledge acquisition. Three research instruments were utilized in this study, namely: Curiosity Inventory, Epistemological Beliefs Inventory, and Mathematics Performance Test. The participants of the study were 167 freshman preservice teachers. Data revealed that mathematics curiosity and epistemological beliefs are significantly related to mathematics performance and they also significantly influence mathematics performance. Â KEY WORD: Psychological factor, epistemological beliefs, mathematics curiosity, preservice teachers,and mathematics performance.Â ABSTRAKSI: â€œKeingintahuan Matematis, Keyakinan Epistemologis, dan Kinerja Matematika Mahasiswa Calon Guruâ€. Ada banyak faktor yang mempengaruhi prestasi akademik mahasiswa. Beberapa hal ini terkait dengan faktor personalogis, sosiologis, dan psikologis. Dalam beberapa tahun terakhir, prestasi dan kinerja akademik telah dikaitkan dengan beberapa faktor psikologis. Dua dari faktor-faktor psikologis yang mungkin memiliki dampak langsung atau pengaruh terhadap kinerja akademis adalah rasa ingin tahu dan keyakinan epistemologis. Studi ini menggambarkan tingkat rasa ingin tahu matematika dan keyakinan epistemologis mahasiswa guru dalam pra-jabatan tahun pertama. Keingintahuan matematika termasuk rasa ingin tahu secara epistemik, persepsi rasa ingin tahu, eksplorasi, dan penyerapan. Keyakinan epistemologis termasuk kepastian pengetahuan, sumber pengetahuan, struktur pengetahuan, pengendalian akuisisi pengetahuan (personal), pengendalian akuisisi pengetahuan (umum), dan kecepatan akuisisi pengetahuan. Tiga instrumen penelitian yang digunakan dalam penelitian ini, yaitu: Inventarisasi Keingintahuan, Inventarisasi Keyakinan Epistemologis, dan Uji Kinerja Matematika. Para peserta penelitian adalah 167 mahasiswa calon guru. Data mengungkapkan bahwa rasa ingin tahu matematika dan keyakinan epistemologis secara signifikan terkait dengan kinerja matematika dan keduanya juga secara signifikan mempengaruhi kinerja matematika.KATA KUNCI: Faktor psikologis, keyakinan epistemologis, rasa ingin tahu matematika, mahasiswa calon guru, dan kinerja matematika.Â Â About the Authors: Rene R. Belecina, Ph.D. is a Full Professor at the College of Graduate Studies and Teacher Education Research PNU (Philippine Normal University). Jose M. Ocampo, Jr., Ph.D. is a Full Professor at the Faculty of Education Sciences PNU (Philippine Normal University). Corresponding authors are: rrbelecina@yahoo.com and juno_6970@yahoo.comHow to cite this article? Belecina, Rene R. Jose M. Ocampo, Jr. (2016). â€œMathematical Curiosity, Epistemological Beliefs, and Mathematics Performance of Freshman Preservice Teachersâ€ in MIMBAR PENDIDIKAN: Jurnal Indonesia untuk Kajian Pendidikan, Vol.1(1) Maret, pp.123-136. Bandung, Indonesia: UPI Press. Chronicle of the article: Accepted (December 13, 2015); Revised (January 29, 2016); and Published (March 11, 2016).